Safety and Efficacy of Early Rehabilitation After Stroke Using Mechanical Thrombectomy: A Pilot Randomized Controlled Trial - Wang, Wei; Wei, Ming; Cheng, Yuanyuan; Zhao, Hua; Du, Hutao; Hou, Weijia; Yu, Yang; Zhu, Zhizhong; Qiu, Lina; Zhang, Tao; Wu, Jialing (Frontiers in Neurology, 2022)
Background Early rehabilitation (ER) has been reported to be both safe and feasible for patients' post-stroke. To date, however, ER-related outcomes concerning patients who have undergone mechanical thrombectomy (MT) have not been investigated. This study aimed to determine the feasibility of ER and whether it improves prognosis in such patients. Methods In this single-center, double-blinded, randomized controlled study involving 103 patients who met the study criteria (i.e., has undergone MT), we randomly divided patients (1:1) into ER and conventional rehabilitation groups. The primary outcome was mortality, while secondary outcomes included favorable outcomes (modified Rankin scale of 0–2), the incidence of non-fatal complications, and Barthel Index (BI) scores. We assessed outcomes at 3 months and 1-year post-stroke. Results No significant between-group differences were found in terms of mortality and favorable outcomes at 3 months and 1-year post-stroke. At 3 months, 15 (28.8%) patients in the ER group and 29 (56.9%) in the conventional rehabilitation group (p = 0.002) had non-fatal complications. The BI in the ER and conventional rehabilitation groups was 100 (85–100) and 87.5 (60–100), respectively, (p = 0.007). At 1 year, the incidence of non-fatal complications was similar between both groups [BI in the ER group, 100 (90–100), p = 0.235; BI in the conventional rehabilitation group, 90 (63.8–100); p = 0.003]. Conclusion Early rehabilitation (ER) reduces the incidence of early immobility-related complications and effectively improves patients' activities of daily living on a short- and long-term basis. Our results indicate that MT contributes to ER in patients with stroke. Clinical Trial Registration www.chictr.org.cn, identifier: ChiCTR1900022665.